Gastroprotective Effect of Ethanolic Extract of Curcuma xanthorrhiza Leaf against Ethanol-Induced Gastric Mucosal Lesions in Sprague-Dawley Rats - Rahim, N.A.; Hassandarvish, P.; Golbabapour, S.; Ismail, S.; Tayyab, S.; Abdulla, M.A. (Hindawi Publishing Corporation, 2014)
Herbal medicines appeared promising in prevention of many diseases. This study was conducted to investigate the gastroprotective effect of Curcuma xanthorrhiza leaf in the rats induced gastric ulcer by ethanol. Normal and ulcer control received carboxymethycellulose (5 mL/kg) orally, positive control was administered with 20 mg/kg omeprazole (reference drug) and 2 groups were received 250 mg/kg and 500 mg/kg of the leaf extract, respectively. To induce of gastric ulcers formation, ethanol (5 mL/kg) was given orally to all groups except normal control. Gross ulcer areas, histology, and amount of prostaglandin E2, superoxide dismutase and malondialdehyde were assessed to determine the potentiality of extract in prevention against gastric ulcers. Oral administration of extract showed significant gastric protection effect as the ulcer areas was remarkably decreased. Histology observation showed less edema and leucocytes infiltration as compared with the ulcer control which exhibited severe gastric mucosa injury. Furthermore, the leaf extract elevated the mucus weight, level of prostaglandin E2 and superoxide dismutase. The extract also reduced malondialdehyde amount significantly. Results showed leaf extract of Curcuma xanthorrhiza can enhanced the gastric protection and sustained the integrity of gastric mucosa structure. Acute toxicity test did not showed any sign of toxicity (2 g/kg and 5 g/kg).